2022
DOI: 10.26554/sti.2022.7.3.269-274
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition using Multiclass Support Vector Machine Method with Local Binary Pattern as Feature Extraction

Abstract: Corn is an essential agricultural commodity since it is used in animal feed, biofuel, industrial processing, and the manufacture of non-food industrial commodities such as starch, acid, and alcohol. Early detection of diseases and pests of corn aims to reduce the possibility of crop failure and maintain the quality and quantity of crop yields. A decision tree is a nonparametric classification model in statistical machine learning that predicts target variables using tree-structured decisions. The performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Local Binary Pattern is an excellent method used for texture analysis which was first introduced by [7]. LBP uses 8 neighboring pixels and 1 central pixel which functions as a threshold value.…”
Section: Local Binary Pattern (Lbp)mentioning
confidence: 99%
See 2 more Smart Citations
“…Local Binary Pattern is an excellent method used for texture analysis which was first introduced by [7]. LBP uses 8 neighboring pixels and 1 central pixel which functions as a threshold value.…”
Section: Local Binary Pattern (Lbp)mentioning
confidence: 99%
“…SVM is a learning system which uses parameters in the form of linear functions to predict or classify. SVM uses a feature space with high dimensions, and uses a learning algorithm based on the implementation optimization theory of statistical learning [7], [9], [22]. SVM is a classification method that is currently widely used and developed by many studies.…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted dimensional calculations using CBCT images and found that measuring the maxillary sinus bone can be utilized for gender identification [15]. Furthermore, a study employed Computed Tomography (CT) images to detect lung nodules, serving as indicators for various lung disorders.…”
Section: Introductionmentioning
confidence: 99%